2020
DOI: 10.1002/14651858.cd012093.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Topical and device-based treatments for fungal infections of the toenails

Abstract: Topical and device-based treatments for fungal infections of the toenails (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 114 publications
3
62
1
Order By: Relevance
“…These treatments do not have definitive guidelines and efficacy results show the greatest variation among all the available options. [76][77][78] Topical antifungals target the fungus from the outside, penetrating from the dorsal nail plate, while systemic medications work from the inside, penetrating the ventral nail plate. Tables 2-5 summarize relevant drug information.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments do not have definitive guidelines and efficacy results show the greatest variation among all the available options. [76][77][78] Topical antifungals target the fungus from the outside, penetrating from the dorsal nail plate, while systemic medications work from the inside, penetrating the ventral nail plate. Tables 2-5 summarize relevant drug information.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…28,[156][157][158] There is limited evidence that lasers eradicate pathogenic fungi because reporting is incomplete, and there is a lack of randomized clinical trials. [76][77][78] Clinical studies have demonstrated the safety and effectiveness of the lasers, but clinical trial data released for lasers are incompletethey do not include the types of infections, details of treatment protocols, mycological or complete cure rates, or relapse rates with follow-up at 12 months post-treatment. In one review, a temporary improvement in nail appearance was seen in 78% of patients during treatment and follow-up.…”
Section: Novel Topical Therapiesmentioning
confidence: 99%
“…Two systematic reviews of treatments for fungal nail infections have been published in recent years [32,33]. In the first of these, Ferrari reported that, although benefits are modest, topical ciclopirox was the best topical preparation for treating toenail infections, concluding that no clinically important results were found from randomized controlled trials of other topical agents such as amorolfine, butenafine, fluconazole, ketoconazole, terbinafine and tioconazole [32].…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…In the most recent systematic review, the Cochrane Skin Group evaluated topical drugs (ciclopirox, efinaconazole, luliconazole and tavaborole) in individuals with toenail onychomycosis [33]. In the case of amorolfine, and although this drug was used as a comparator in some of the included trials, the systematic review was unable to assess the quality of the evidence due to the lack of any randomized controlled trials conducted or published that included amorolfine as the intervention of interest [33]. The authors concluded that while the overall evidence supports the use of topical therapies, complete cure rates were relatively low.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation